DEVELOPMENT OF SCRATCH-ASSISTED TEACHING MATERIALS TO DEVELOP COMPUTATIONAL THINKING SKILLS IN ELEMENTARY SCHOOLS - Rahmawati, Anis; Dindin Abdul Muiz Lidinillah; Asep Nuryadin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to develop a Scratch-assisted module of flat building material to develop computational thinking skills in elementary schools. This research uses the R&D (Research and Development) method with the EDR (Educational Design Research) research model which consists of three stages, namely analysis and exploration; design and construction; evaluation and reflection. Data collection in this study was obtained from the results of validation tests on three material experts (mathematics and informatics materials), one learning media expert, one programming expert, and one pedagogical expert. In addition, data collection was also obtained from the results of student response questionnaires after learning using the Scratch programming module. Data analysis techniques use descriptive qualitative and quantitative. The results of the product feasibility trial from the validator of mathematical materials obtained a percentage score of 77.75% including the feasible category; Informatics material expert validators obtained a score of 86.7% in the very decent category; Learning media expert validators obtained a score of 90% in the very decent category; Expert Programming Validators obtained a score of 96.9% in the very decent category; pedagogical expert validators obtained a score of 76% in the decent category; and the student response questionnaire obtained results of 91.25% with a very decent category. Based on the results of the research conducted, the teaching materials developed, namely the Scratch-assisted module, flat building material are very feasible to be used to help develop computational thinking skills in elementary schools